Completing the Enalaprilat Excretion Pathway-Renal Handling by the Proximal Tubule - Nori J. L. Smeets; Carlijn H. C. Litjens; Jeroen J. M. W. van den Heuvel; Hedwig van Hove; Petra van den Broek; Frans G. M. Russel; Jan B. Koenderink; Saskia N. de Wildt (MDPI AG, 2020)
Background: Enalapril is often used in the treatment of cardiovascular diseases. Clinical data suggest that the urinary excretion of enalaprilat, the active metabolite of enalapril, is mediated by renal transporters. We aimed to identify enalaprilat specificity for renal proximal tubular transporters. Methods: Baculovirus-transduced HEK293 cells overexpressing proximal tubular transporters were used to study enalaprilat cellular uptake. Uptake into cells overexpressing the basolateral transporters OCT2, OAT1, OAT2, or OAT3 and apical transporters OAT4, PEPT1, PEPT2, OCTN1, OCTN2, MATE1, MATE2k, and URAT1 was compared with mock-transduced control cells. Transport by renal efflux transporters MRP2, MPR4, P-gp, and BCRP was tested using a vesicular assay. Enalaprilat concentrations were measured using LC-MS/MS. Results: Uptake of enalaprilat into cells expressing OAT3 as well as OAT4 was significantly higher compared to control cells. The enalaprilat affinity for OAT3 was 640 (95% CI: 520-770) µM. For OAT4, no reliable affinity constant could be determined using concentrations up to 3 mM. No transport was observed for other transporters. Conclusion: The affinity of enalaprilat for OAT3 and OAT4 was notably low compared to other substrates. Taking this affinity and clinically relevant plasma concentrations of enalaprilat and other OAT3 substrates into account, we believe that drug-drug interactions on a transporter level do not have a therapeutic consequence and will not require dose adjustments of enalaprilat itself or other OAT3 substrates.